Albumin‐myosteatosis gauge as a novel prognostic risk factor in patients with non‐metastatic colorectal cancer. Issue 2 (25th January 2023) - Kim, Yerim; Lee, Jae‐Hoon; Cho, Eun‐Suk; Lee, Hye Sun; Shin, Su‐Jin; Park, Eun Jung; Baik, Seung Hyuk; Lee, Kang Young; Kang, Jeonghyun
Abstract: Background: Myosteatosis and systemic inflammation are well‐known prognostic factors in patients with colorectal cancer (CRC). The serum albumin level is a reflection of malnutrition and systemic inflammation, which in turn plays a key role in the development of myosteatosis. However, few studies have been conducted on these synergistic effects. This study aimed to examine the individual and synergistic effects of different prognostic markers related to skeletal muscle quality and serum albumin levels in patients with CRC. Methods: This study enrolled patients with stage I–III CRC who underwent surgical resection between July 2006 and February 2014. Skeletal muscle index (SMI) and skeletal muscle radiodensity (SMD) were calculated using computed tomography at the L3 level obtained within 2 months prior to surgery. The albumin‐myosteatosis gauge (AMG) was defined as SMD × albumin. Patients were divided into sex‐specific quartiles (G1 to G4) according to the AMG, and analysis of variance for continuous variables and chi‐square test for categorical variables were used to compare variables among quartiles. Cox proportional hazard models were constructed and integrated receiver operating characteristic curve (iAUC) analysis was used to compare the prognostic performance of SMD, albumin and AMG. Results: Among the 906 participants, the median (interquartile) age was 64 (55–72) years, and 365 (40.3%) were female. AMG was significantly correlated with the occurrence of complications, albumin level, SMI and SMD (all P < 0.001). Overall survival (OS) differed significantly according to the AMG group, with 5‐year OS for G1–G4 being 73.4%, 86.2%, 91.1% and 95.5%, respectively ( P < 0.0001). Although SMI, SMD, albumin and AMG were all significant individual prognostic markers of OS in the univariable analysis, AMG remained the only independent prognostic factor in the multivariable analysis (G1 vs. G2, P = 0.045, G1 vs. G3, P = 0.005, G1 vs. G4, P < 0.001, respectively). The iAUC value of AMG [0.681, 95% confidence interval (CI) = 0.638–0.723] was superior to that of SMD (0.610, 95% CI = 0.566–0.654) (bootstrap iAUC mean difference = 0.071, 95% CI = 0.034–0.106), SMI (0.551, 95% CI = 0.511–0.594) (bootstrap iAUC mean difference = 0.129, 95% CI = 0.076–0.181) and albumin (0.627, 95% CI = 0.585–0.668) (bootstrap iAUC mean difference = 0.053, 95% CI = 0.010–0.098). Conclusions: In patients with stage I–III CRC, AMG is a meaningful predictor of survival, with superior prognostic value compared to SMI, SMD or albumin alone. Further studies are needed to determine their significance in different ethnic groups.